New syllabus primary Mathematics workbook 3B - Yee , Foong Pui; Lim Li Gek Pearlyn; Wong Oon Hua (Karachi : Oxford university press, 2019)
The "Primary Mathematics Workbook 3B" (typically based on the Singapore Math curriculum) is designed for students around the age of 9, and it usually covers more advanced concepts within the realm of elementary mathematics. The workbook focuses on building strong mathematical foundations through problem-solving and practice exercises.
Keywords: Mathematics workbook 3B; Oxford Mathematics workbook 3B